Reducing Academic Stress Using Online Counseling based on Acceptance and Commitment Therapy - Syifa, Layyinatus; Mulawarman, Mulawarman; Sunawan, Sunawan (Universitas Negeri Semarang, 2022)
Students’ stress management is needed in order to obtain optimum achievement. This study was focused on reducing academic stress through online counseling based on an acceptance and commitment therapy approach. 20 Vocational High School (SMK) students were chosen using purposive sampling technique and divided into four groups for pretest, posttest, and follow up. Their data were collected using the Perception of Academic Stress Scale and examined in mixed manova test to compare the effectiveness of the treatment in experimental and control groups. Findings showed that the online counseling based on an acceptance and commitment therapy approach was able to reduce students’ academic stress. In addition, the combination of two kinds of counseling, namely synchronous and asynchronous gave the most optimum results. Also, this study further explored the interaction between counselors and counselees in web-based ACT intervention to reduce academic stress.